Ultrafast Multilevel Switching in Au/YIG/n‐Si RRAM. (19th November 2018) - Chen, Zhiwei; Huang, Weichuan; Zhao, Wenbo; Hou, Chuangming; Ma, Chao; Liu, Chuanchuan; Sun, Haoyang; Yin, Yuewei; Li, Xiaoguang
Abstract: Resistive random access memory (RRAM) with ultrafast and multilevel switching is extremely promising for next‐generation nonvolatile memory. Here, ultrafast unipolar resistive switchings (≈540 ps) with high off/on resistance ratio (≈10 4 ) are obtained in yttrium iron garnet Y3 Fe5 O12 (YIG)‐based resistive memory on n‐Si substrate. The sub‐nanosecond operation is also successfully performed up to 85 °C with an off/on resistance ratio of ≈10 3 . In addition, by using different compliance currents for the set process, five discrete resistance levels with ultrafast switchings among them are achieved and the multilevel states show reliable retention (>10 4 s). The large, stable, reproducible, and reliable switching behaviors of the Au/YIG/n‐Si RRAM cell shows its great potential for ultrafast multilevel memory applications. Abstract : By fabricating an Au/YIG/n‐Si resistive random access memory (RRAM) on silicon, ultrafast unipolar resistive switchings (≈540 ps) with high off/on resistance ratio are demonstrated at both room temperature and 85 °C. Five discrete resistance levels with ultrafast switchings are obtained and show reliable retention. Such an ultrafast multilevel unipolar RRAM is promising for ultrafast multilevel memory applications.